DISABILITY STATUS AND VICTIMIZATION: AN EXAMINATION OF MEDIATING FACTORS ON RISK - Gann, Taylor L (2018)
Current estimates of the world’s population demonstrate that approximately 15-19 percent of individuals possess some form of disability (Hughes et al., 2012). Studies examining the victimization risk of this group have found that the disabled are approximately two times more likely to experience victimization, as compared to their non-disabled counterparts (Emerson & Roulstone, 2015; Sobsey, 2014). In addition to the increased likelihood of victimization, researchers have documented variation in risk across different disability statuses (Kahlifeh et al., 2013; Turner et al., 2011). Although there is evidence of a differentiation in risk, reasons behind this variation have been neglected. Furthermore, studies regarding the victimization of some forms of disability, such as the hearing impaired, have been limited. Utilizing Cohen and Felson’s (1969) routine activities theory, a series of multivariate logistic regressions were conducted employing data from the Life Opportunities Survey collected in the U.K. The first step in the analysis was to establish victimization risk across disability statuses. Second, target suitability, guardianship, and exposure factors associated with varying forms of impairment were incorporated to account for any potential mediation of the association between disability status and the outcome variable, victimization. I found that there is significant variation in risk across disability statuses. In addition, aspects of routine activities/lifestyles vary significantly across different forms of disability. Conversely, these elements did not mediate the relationship between disability status and victimization